PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP TINGKAT KEPUASAN MASYARAKAT DI KANTOR KECAMATAN TANJUNG SELOR KABUPATEN BULUNGAN - Helen Sintia dan Maskan (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
The Effect of Quality of Public Service on The Level of Community Satisfaction in Tanjung Selor Sub-District Office of Bulungan Regency. This study aims to find out how the Influence of Public Service Quality on The Level of Community Satisfaction in the District Office Tanjung Selor Bulungan Regency.The results showed that there is a positive and significant relationship between public service variables and community satisfaction variables in the District Office of Tanjung Selor Bulungan Regency. This can be seen from the results of statistical tests where the coefficient of regression X of 0.826 states that every addition of 1% of the value of Public Servants, the value of Public Satisfaction increases by 0.826. The regression coefficient is positive, so it can be said that the direction of the influence of variable X on variable Y is positive.Then based on the results of the Hypothesis Test can be explained that the amount of correlation value r calculate or relationship (R) is 0.766. Price r table for error level of 5% with n = 36 obtained 0.329 and for 1% = 0.424. Since the price of r calculates greater than the table r for both errors of 5% and 1% (0.766 > 0.424 > 0.329), it can be concluded that there is a positive and significant relationship of 0.766 between Public Service and Public Satisfaction. From the output above obtained the result of coefficient of determination (R Square) of 0.587 which contains the understanding that the influence of public service variables (X) on Public Satisfaction (Y) is 58.7% This means the influence of Public Service variables (X) on Public Satisfaction (Y) is large / significant, the remaining 41.3% is determined by other factors not studied in the study.Meanwhile, based on coefficients table which is the output of Simple Linear Regression Test can be taken that, from the table Coefficients obtained a value less than 0.005 ( 0.001 < from 0.005) so that it can be concluded that the hypothesis in this study can be proven to be true. Then based on the value of t-count, it can be known that the value of t-count of 6951 is greater t-table 2.02809 so that it can be concluded that public service variable (X) affects the variable Community Satisfaction (Y).So it can be concluded that there is a positive and significant influence of public service variables with public satisfaction variables, thus it can also be said that the formulation of problems in the research has been answered and the hypothesis proposed has proven to be correct.